Investigation of Aflatoxin B1, Ochratoxin A, and Fumonisin B1 in Poultry Feeds in ‎Nineveh Province - Alnaemi, Hiba; Dawood, Tamara; Algwari, Qais (The Iraqi Journal of Veterinary Medicine, 2023)
Aflatoxin B1 (AFB1), ochratoxin A (OTA), and fumonisin B1 (FB1), the most commonly ‎encountered mycotoxins, constitute serious human ‎and animal health threats as a result of their ‎toxigenic, carcinogenic, and mutagenic influences‎. The study aimed to investigate the occurrence ‎of these mycotoxins in poultry feeds and determine the ‎percentage of the samples that exceeded the legal limits approved by the European ‎Commission ‎‎(EC). Sixty poultry feed samples were collected from poultry feed plants and poultry farms in Nineveh ‎Province and analyzed for ‎detection mycotoxins‏ ‏using competitive Enzyme-Linked Immunosorbent ‎Assay (ELISA). Results reported co-occurrence of AFB1 and FB1 in ‎all samples examined (100%), while AFB1, ‎OTA, and FB1 co-occurred in 53 samples (88.33%) at values ranging between 3.15–43.96, 0–‎‎168.24, ‎and 220.6–6935.12 ppb, respectively. Also, results showed that FB1 existed at a mean value (2164.01 ‎ppb) significantly higher ‎‎(P<0.05) than those reported for AFB1 and OTA (16.48 and 32.09 ppb, ‎respectively). Results revealed that 38.33% and 10% of feed samples ‎exceeded the maximum ‎permissible limits for AFB1 and OTA established by EC, whereas all feed samples were within the ‎EC limit for FB1. As ‎a result, strict procedures should be implemented to achieve legal limits concerning AFB1 and ‎OTA in poultry feeds to preserve public health.